EXTERNAL REPRESENTATION FLEXIBILITY OF DOMAIN AND RANGE OF FUNCTION - Aziz, Tian Abdul; Kurniasih, Meyta Dwi (Journal on Mathematics Education, 2019)
This study attempts to analyze pre-service secondary mathematics teachers’ flexibility of external representations of domain and range of functions. To reach the purpose, a task consisted of thirty question items were designed. Participants of the study were thirty-eight Indonesian pre-service secondary mathematics teachers attending mathematics education department at one private university in Jakarta, Indonesia. Based on the analysis participants written responses, this paper revealed participants’ difficulties in providing a proper and consistent definition of the concept of domain and range of functions. We also disclosed the participants’ lack of flexibility in doing translation among representations under the concept of domain and range of function. In general, participants written responses to the task did not provide evidence of a solid understanding of domain and range. There are several implications of these findings offered for secondary mathematics teacher education’s program.